2014
DOI: 10.3892/br.2014.287
|View full text |Cite
|
Sign up to set email alerts
|

Effect of RANTES gene promoter genotypes in patients with ulcerative colitis

Abstract: Abstract.A complex interaction of genetic and environmental factors is closely associated with the development of inflammatory bowel disease. Previous studies reported that the expression of the regulated upon activation, normal T-cell expressed and secreted (RANTES) gene is enhanced in the colonic mucosa of ulcerative colitis (UC). Quantitative differences in RANTES gene expression among numerous promoter genotypes have also been reported. The aim of the present study was to clarify the effect of RANTES promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…While a number of studies have shown the importance of DNA methylation in EMT, these studies used traditional bisul te treatment to measure 5mC, which does not resolve 5hmC (20)(21)(22)(23)(24)(25). 5hmC can be estimated from comparing oxidized-bisul te treatment to bisul te treated DNA (26), as traditional bisul te treatment does not distinguish 5mC from 5hmC.…”
Section: Introductionmentioning
confidence: 99%
“…While a number of studies have shown the importance of DNA methylation in EMT, these studies used traditional bisul te treatment to measure 5mC, which does not resolve 5hmC (20)(21)(22)(23)(24)(25). 5hmC can be estimated from comparing oxidized-bisul te treatment to bisul te treated DNA (26), as traditional bisul te treatment does not distinguish 5mC from 5hmC.…”
Section: Introductionmentioning
confidence: 99%